1999
DOI: 10.1002/(sici)1097-4628(19990418)72:3<361::aid-app6>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rare earth compounds as fillers on friction and wear behaviors of PTFE-based composites

Abstract: ABSTRACT:The friction and wear behaviors of polytetrafluoroethylene (PTFE)-based composites filled with rare earth compounds CeO 2 , CeF 3 , and La 2 O 3 in volume content from 5 to 30% sliding against GCr15 bearing steel under dry friction conditions were evaluated by using an MHK-500 ring-block wear tester. The wear debris and the worn surfaces of the PTFE composites were investigated by using a scanning electron microscope (SEM), whereas the transfer films of the PTFE composites formed on the surface of GCr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Fabrics were treated with rare earths CeO 2 , LaCl 3 , La 2 O 3 and CeF 3 by Shen, Zhan and some scholars, and their friction, wear properties and bonding properties of the joint bearings with the modified rare earths were studied. The results shown that the bonding strength was higher under the action of rare earths, the film formation is faster, and the coefficient of friction is generally less than 0.1 [13][14][15][16]. Liners and adhesive glue as the main component cannot be used at medium and high temperatures, and the bonding liner method is generally applicable to small thick-walled sliding bearings, which has certain limitations for medium and large sliding bearings.…”
Section: Adhesive Liner For Self-lubricating Bearingmentioning
confidence: 99%
“…Fabrics were treated with rare earths CeO 2 , LaCl 3 , La 2 O 3 and CeF 3 by Shen, Zhan and some scholars, and their friction, wear properties and bonding properties of the joint bearings with the modified rare earths were studied. The results shown that the bonding strength was higher under the action of rare earths, the film formation is faster, and the coefficient of friction is generally less than 0.1 [13][14][15][16]. Liners and adhesive glue as the main component cannot be used at medium and high temperatures, and the bonding liner method is generally applicable to small thick-walled sliding bearings, which has certain limitations for medium and large sliding bearings.…”
Section: Adhesive Liner For Self-lubricating Bearingmentioning
confidence: 99%
“…It is suggested that, in friction process, La Oxide (La 2 O 3 ) and La Fluoride (LaF 3 ) will be produced in tribochemical reaction because the element La exists on the frictional interface. La Oxide and La Fluoride both have low hardness and excellent lubrication properties [17]. Under dry sliding condition, these two La compounds can act as lubrication to CF/PTFE composites; therefore, the tribological properties of the composite are improved.…”
Section: The Mechanism Of Effects Of Re Treatment On Tribological Promentioning
confidence: 99%
“…Among the various metal-oxide reinforcement particles, CeO 2 can be attractive due to its special physical and chemical characteristics. CeO 2 particles have been used as fillers for fabricating polytetrafluoroethylene-based composites where the tribological properties of the fabricated composites were improved significantly at high temperatures [21][22][23]. The co-deposition of CeO 2 particles with Ni has been reported in a few articles.…”
Section: Introductionmentioning
confidence: 99%